2013
DOI: 10.1115/1.4025109
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and ex Vivo Approaches to Studying the Biomechanical Properties of Healing Wounds in Rat Skin

Abstract: An evaluation of wound mechanics is crucial in reflecting the wound healing status. The present study examined the biomechanical properties of healing rat skin wounds in vivo and ex vivo. Thirty male Sprague-Dawley rats, each with a 6 mm full-thickness circular punch biopsied wound at both posterior hind limbs were used. The mechanical stiffness at both the central and margins of the wound was measured repeatedly in five rats over the same wound sites to monitor the longitudinal changes over time of before wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Polarization-sensitive optical coherence tomography (PS OCT) is non-destructive, reflection-based imaging modality that has been shown 2, 9, 14 to provide depth-resolved structural characteristics of biological tissues. The current study shows the use of phase retardance images produced by polarization-sensitive optical coherence tomography (PS OCT) for providing the means for marker-free, high-resolution 3D motion tracking of the lumbar facet capsular ligament (FCL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polarization-sensitive optical coherence tomography (PS OCT) is non-destructive, reflection-based imaging modality that has been shown 2, 9, 14 to provide depth-resolved structural characteristics of biological tissues. The current study shows the use of phase retardance images produced by polarization-sensitive optical coherence tomography (PS OCT) for providing the means for marker-free, high-resolution 3D motion tracking of the lumbar facet capsular ligament (FCL).…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a non-destructive, depth-resolved, back-scattering/reflection-based imaging technique that has been used previously in mechanical investigations of wound healing 9 , tissue folding 14 , and thermal denaturation of collagen 2, 11 . Importantly, Filas et al 13, 14 used OCT images of the embryonic chick heart with microspheres as markers to track tissue deformation, and Li et al 20 used OCT for gross strain and strain rate estimates based on heart wall thickness changes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent progress in evaluating MSC based therapies for wound healing, the distinct interaction of MSCs with the mechanical and chemical cues present in wound bed is not fully understood and this currently limits the extensive use of MSCs in clinical capacity. Previous studies have reported that wound stiffness increases dramatically during the healing process and modifies the function of underlying cells, e.g., fibroblasts, in both normal and pathological conditions (Goffin et al, 2006; López et al, 2010; Liu et al, 2010a; Chao et al, 2013; Klingberg et al, 2013; Darby et al, 2014). In addition to the biochemical signals present in the wound milieu, such mechanical cues e.g., matrix elasticity, can also affect the MSC function profoundly (Engler et al, 2006; Kilian et al, 2010; Tse and Engler, 2011; MacQueen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we incorporated optical coherence tomography (OCT)[ 26 , 27 ] into our indentation system[ 28 ], and we used this novel OCT-indentation system to determine the impact of FD-induced high myopia on in-situ corneal biomechanical properties (CB), while IOP was maintained constant at one of three values in the physiological range. This system was designed with attention to the anatomical features of our target animal model, the chicken; namely: 1) the indenter probe was miniaturized (1 mm diameter) because of the steep corneal curvature in our small animals; 2) crystalline lens surface was used as a reference (see details in Methods ), to avoid confounding error due to eyeball movement during corneal indentation[ 29 ]; and 3) time-domain OCT (TD-OCT) was incorporated, to provide fast, high-resolution tracking of corneal and crystalline lens surfaces during indentation at different IOPs.…”
Section: Introductionmentioning
confidence: 99%